2021
DOI: 10.1039/d1ra00410g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of superhydrophobic nylon-56/cotton-interwoven fabric with dopamine-assisted use of thiol–ene click chemistry

Abstract: Preparation process of superhydrophobic textiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…There have been fewer studies published on bio‐based PA56 compared with those on PA6 and PA66. To date, some studies on improving the properties of bio‐based PA56 composites have been reported, such as on the improvement of their mechanical properties and yellowing resistance 10,21,22 . There have been few reports on improving the heat resistance of bio‐based PA56.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been fewer studies published on bio‐based PA56 compared with those on PA6 and PA66. To date, some studies on improving the properties of bio‐based PA56 composites have been reported, such as on the improvement of their mechanical properties and yellowing resistance 10,21,22 . There have been few reports on improving the heat resistance of bio‐based PA56.…”
Section: Introductionmentioning
confidence: 99%
“…To date, some studies on improving the properties of bio-based PA56 composites have been reported, such as on the improvement of their mechanical properties and yellowing resistance. 10,21,22 There have been few reports on improving the heat resistance of bio-based PA56. N-phenyl maleic imide (NPMI) has a structure that features planar five-membered rings and rigid benzene rings, 23,24 therefore, adding it to the molecular chain of a polymer can increase the internal rotation resistance between the molecular chains and improve the heat resistance of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-based PA56 is derived from renewable resources such as wheat and corn, produced by a microbial process, and then synthesized with adipic acid. [1][2][3] Compared with traditional amide nylon 66, PA56 has the advantages of low carbon and environmental protection. Its performance is comparable to that of traditional thermoplastic PA66, and even better than PA66 in some aspects.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used in many fields, such as engineering plastics, food packaging, electronic instruments, and automotive parts. Bio‐based PA56 is derived from renewable resources such as wheat and corn, produced by a microbial process, and then synthesized with adipic acid 1–3 . Compared with traditional amide nylon 66, PA56 has the advantages of low carbon and environmental protection.…”
Section: Introductionmentioning
confidence: 99%